Inverse Iteration Algorithm for Neutron Depth Profiling - SHI Cong (Journal of Isotopes, 2017)
Based on the method of Monte Carlo simulation and probabilistic inversion for neutron depth profiling, the depth concentration distribution of element B in Si matrix material was calculated. According to NDP experimental equipment at CARR, energy spectra of standard sample SRM2137 were simulated by using MCNP and Geant4 software, and the concentration-depth diagram of elements in SRM2137 was achieved adopting inverse iteration method through MATLAB software. It showed that the inverse iteration calculation in NDP was feasible.